Thalidomide as Treatment of Lip’s Pyogenic Granuloma - Lai L; Nie J; Duan D; Huang D (International Medical Case Reports Journal)
Liyan Lai,1,* Jiayao Nie,2,* Dejian Duan,3 Dan Huang2 1The Seventh Clinical College of Guangzhou University of Chinese Medicine, Shenzhen, Guangdong, People’s Republic of China; 2Department of Dermatology, Shenzhen Traditional Chinese Medicine Hospital, Shenzhen, Guangdong, People’s Republic of China; 3Department of Dermatology, Shenzhen Bao’an Chinese Medicine Hospital, Shenzhen, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dejian Duan, Department of Dermatology, Shenzhen Bao’an Chinese Medicine Hospital, 25 Yu’an 2nd Road, 30 District, Baoan District, Shenzhen, Guangdong, People’s Republic of China, Email Oldduan2000@163.comAbstract: Pyogenic granuloma (PG) is a benign vascular tumor that can be challenging to treat, particularly in aesthetically sensitive areas. We report a case of a 32-year-old man with a PG on the upper lip that did not respond to conventional treatments, including glucocorticoid injections and long-pulse 1064 nm laser therapy. Due to aesthetic concerns and the lack of response to these treatments, the patient was administered oral thalidomide at a nightly dose of 75 mg for 5 months, which resulted in complete regression without recurrence over a 3-year follow-up. This case suggests thalidomide’s potential as an effective alternative treatment for PG in sensitive areas.Keywords: pyogenic granuloma, thalidomide, treatment, lip